Thermal Analysis of Insulation Design for a Thermal Energy Storage Silo Containment for Long-Duration Electricity Storage - Gifford, Jeffrey; Ma, Zhiwen; Davenport, Patrick (Frontiers in Energy Research, 2020)
Greater renewable energy penetration requires increasing energy storage capacity. Long-duration energy storage (LDES) will be required to balance intermittent renewable energy supply with daily, weekly, and even seasonal supply changes. At these timescales, traditional electrochemical batteries become uneconomical. Solid-particle thermal energy storage (TES) is a viable solution to this issue. Solid particles can achieve higher temperatures (>1100°C) than the molten salt used in traditional concentrated solar power (CSP) TES systems. Higher temperatures yield higher power cycle thermal-electrical conversion efficiencies. However, at these higher temperatures, greater heat loss and insulation material cost could negate the efficiency benefits. In this work, the insulation design of a full-size 3D containment silo capable of storing 5.51 GWht for the purpose of LDES for grid electricity was thermally analyzed. Proposed operating conditions were simulated using transient FEA methods. After five days (120 hours) of storage, less than 3% thermal energy loss was achieved at a design storage temperature of 1200°C. Material thermal limits were considered and met. Sensitivity of the storage system’s performance to operational, climate, and temporal changes were also studied. These changes had minimal impacts on the thermal efficiency of the system but did have meaningful implications for other aspects of the insulation design.